Efeitos da fração proteolítica - P1G10- derivada do látex de Vasconcellea cundinamarcensis sobre o reparo ósseo: proliferação e diferenciação de osteoblastos. - Verlane Gonçalves Santos (2014)
P1G10 is a proteolytic fraction obtained from Vasconcellea cundinamarcensis latex, which shows skin and gastric healing activities in lesions of different etiologies. In this study, we aimed to evaluate bone repair activity of this fraction using a model of intraoral bone defect in rats, showing a probable involvement of proliferation and differentiation of osteoblasts promoted by the treatment with subfraction CMS2 and protease CMS2MS3, purified from P1G10. Histological analysis of bone injury performed with the aid of a drill on the maxillary first molar of Wistar rats showed no changes in the different experimental groups regarding the inflammatory infiltrate (discrete) and number of vessels in a period of 14 days. On the other hand, was observed the increased bone formation after 7 days of treatment with P1G10 at 0.01 and 0.05% w/v (20.5% and 26.0%, respectively) equaling the other experimental groups at 14 days. Analysis in vitro showed that exposure of primary osteoblasts at CMS2 (10-100 ng/ml) and CMS2MS3 (10 and 50 ng/ml) induced a mitogenic effect on these cells (approximately 13 and 32%, respectively). In addition, cell differentiation was also stimulated by treatment with CMS2 and CMS2MS3 (0.1-10 ng/ml) when assessed by activity of the alkaline phosphatase (ALP) (about 12%) and the mineralization of the extracellular matrix (about 50 and 60%, respectively). Thus, we suggest that bone formation promoted by P1G10 fraction may be bound to a stimulation of proliferation and differentiation of osteoblasts, since these cells are intimately involved in bone formation.